2007
DOI: 10.1113/jphysiol.2007.139584
|View full text |Cite
|
Sign up to set email alerts
|

Neural drive to human genioglossus in obstructive sleep apnoea

Abstract: One postulated mechanism for obstructive sleep apnoea (OSA) is insufficient drive to the upper-airway musculature during sleep, with increased (compensatory) drive during wakefulness. This generates more electromyographic activity in upper airway muscles including genioglossus. To understand drives to upper airway muscles, we recorded single motor unit activity from genioglossus in male groups of control (n = 7, 7 ± 2 events h −1 ) and severe OSA (n = 9, 54 ± 4 events h −1 ) subjects. One hundred and seventy-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 61 publications
3
104
0
2
Order By: Relevance
“…To determine the depth and location for the recording electrodes in genioglossus, the local anatomy of the upper airway musculature was examined with ultrasonography (12L highfrequency linear array transducer, Vivid i GE Healthcare, Chalfont St. Giles, Bucks, UK) (14,38,39). The distance from the skin to the inferior margin of the genioglossus and geniohyoid muscles and the lateral width of genioglossus were recorded using an electronic caliper (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the depth and location for the recording electrodes in genioglossus, the local anatomy of the upper airway musculature was examined with ultrasonography (12L highfrequency linear array transducer, Vivid i GE Healthcare, Chalfont St. Giles, Bucks, UK) (14,38,39). The distance from the skin to the inferior margin of the genioglossus and geniohyoid muscles and the lateral width of genioglossus were recorded using an electronic caliper (14).…”
Section: Methodsmentioning
confidence: 99%
“…4) (38,39). Briefly, all units were classified into tonic or phasic categories, depending on whether they discharged throughout both inspiration and expiration (tonic), or only during either inspiration or expiration (phasic).…”
Section: ) Cpap Was Terminatedmentioning
confidence: 99%
“…Although the GG is considered to be a single muscle, its fan-like fibre orientation results in different mechanical activity depending on the fibres recruited [34]. Recent studies that have evaluated single motor-units of the GG have shown that this muscle's EMG is composed of several populations of units that are activated differently during breathing [29,43]. These motor units are coordinated by complex premotor networks [29,44] that may be affected by anaesthesia [45].…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 99%
“…Another characteristic of the UA muscles is the high percentage disproportion of glycolytic fast twitch of type II muscle fibers compared with non-OSA control subjects [12,14,55,[59][60][61][62], a difference that may represent an adaptive response to mechanical strain and/or neuronal activity. In this way, the over expression of N-CAM is suggestive of collateral nerve sprouting, reflected in the hyperinnervation that present these muscles [13].…”
Section: Muscle Changes In Osasmentioning
confidence: 99%